Case 29-2015: A 38-Year-Old Pregnant Woman With Headache and Visual Symptoms. Issue 2 (June 2016) - Feske, Steven K.; Goldberg, Marcia; Dudzinski, David M.; Gonzalez, Ramon Gilberto; Kovach, Alexandra E.
Abstract : ( N Engl J Med . 2015;373:1154–1164) In this case report, a 38-year-old pregnant woman (gravid 2, para 0) was admitted to the hospital at 33 weeks 3 days of gestation because of occipital headache, vomiting, a 2-minutes spell with visual symptoms (tunnel vision, spots in the visual field, unsteadiness, and vertigo) and hyperventilation.